Salmonella enterica in internal organs of cattle and comparative growth of Fusobacterium necrophorum subspecies and Fusobacterium varium in lactate- and/or lysine-based enrichment media - Baghaei Naeini, Farinaz (My University, 2025)
This report provides a review of prevalence and distribution of Salmonella enterica in internal organs of cattle and two experimental studies on Fusobacterium species associated with liver abscesses. The review highlights that S. enterica primarily colonizes the gastrointestinal tract of cattle and can also spread to internal organs such as the lymph nodes, liver, and lungs, where it can persist as hidden reservoirs, often causing asymptomatic infections that contribute to beef contamination during slaughter. Among the major serotypes of S. enterica, S. Dublin, S. Typhimurium, and S. Newport are frequently linked to systemic infections and foodborne outbreaks. The review includes the zoonotic significance of Salmonella, its persistence in internal organs, and the challenges of controlling contamination in beef production systems. Key preventive strategies include improving farm hygiene, strengthening biosecurity, vaccination, and adopting proper processing and handling practices to reduce bacterial transmission and protect public health. Chapter 2 focuses on Fusobacterium necrophorum and F. varium involved in bovine liver abscesses and includes two experimental studies. The study 1 was on the detection and quantification of F. necrophorum subsp. necrophorum and F. necrophorum subsp. funduliforme in bovine tissues (healthy livers, abscessed livers, ruminal epithelial and colonic epithelial) and comparison of three enrichment media, Peptone-Yeast extract with lactate, lysine or both; PY-La, Py-Ly, and PY-La-Py). The enrichment containing both lactate and lysine yielded the highest recovery of F. necrophorum subspecies, especially from ruminal and colonic tissues, while lysine broth was most effective for liver abscesses. The study 2 was on comparative growth of F. necrophorum subsp. necrophorum, F. necrophorum subsp. funduliforme, and F. varium in PY-La, PY-Ly, and PY-Ly-La broths, which examined bacterial growth under anaerobic conditions and found that both F. necrophorum subspecies grew best in PY-Ly-La broth, while F. varium exhibited the highest growth in PY-Ly broth, indicating distinct substrate utilization patterns. Together, these findings demonstrate that Salmonella and Fusobacterium are major pathogens impacting cattle health and in addition, Salmonella is a major foodborne pathogen with implications in beef safety. Understanding the persistence of Salmonella in internal organs provides insight for developing more effective control and monitoring programs, while identifying the most effective enrichment medium capable of detecting and quantifying low concentrations of Fusobacterium provides a more accurate insight into its distribution in cattle tissue samples
Keywords: Salmonella; Fusobacterium; Lactate; Lysine